2022
DOI: 10.1186/s13244-022-01200-z
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of localized pneumonic-type lung adenocarcinoma and pulmonary inflammatory lesion

Abstract: Background In clinical practice, a number of delayed diagnoses of localized pneumonic-type lung adenocarcinoma (L-PLADC) mimicking pneumonia have been identified due to the lack of knowledge regarding the radiological findings associated with this condition. Here, we defined L-PLADC as a special type of lung adenocarcinoma that presents as a focal consolidation involving < 50% of the area of a lobe and aimed to investigate the differential clinical and imaging features between L-PLADC and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
1
7
1
Order By: Relevance
“…In addition, the findings of this study suggested that calcification, satellite lesions, and thickening of the adjacent bronchial wall and interlobular septum were more common in inflammatory lesions, which may be related to the diffusion of inflammation along the adjacent alveoli, bronchi, and mesenchyme. In contrast to the literature ( 3 ), the proportion of calcification and satellite lesions in this group was slightly higher, as was the proportion of pulmonary tuberculosis cases, which may be related to the relatively high incidence of calcification and surrounding satellite lesions in tuberculosis. Similarly, pleural thickening and pleural effusion were also highly indicative of inflammatory lesions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, the findings of this study suggested that calcification, satellite lesions, and thickening of the adjacent bronchial wall and interlobular septum were more common in inflammatory lesions, which may be related to the diffusion of inflammation along the adjacent alveoli, bronchi, and mesenchyme. In contrast to the literature ( 3 ), the proportion of calcification and satellite lesions in this group was slightly higher, as was the proportion of pulmonary tuberculosis cases, which may be related to the relatively high incidence of calcification and surrounding satellite lesions in tuberculosis. Similarly, pleural thickening and pleural effusion were also highly indicative of inflammatory lesions.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results also showed that necrosis is more common in inflammatory lesions, which is consistent with the findings of previous studies ( 3 , 8 ). Inflammatory necrosis is related to the inflammatory response caused by microbial infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…7,8 The diagnosis was made by analyzing the morphological variation in the cancerous area, quantifying the density of the malignant area, and observing the spatial arrangement of the tumor microenvironment. [9][10][11] Nevertheless, the scarcity of pathologists and high clinical experience requirements exacerbate the conflict between clinical demands and actual production. In addition, intra-and inter-observer differences introduce additional bias and risk to histopathological analysis in the diagnostic processes.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of routine diagnosis, digital whole slide image (DWSI) of hematoxylin and eosin (H&E) stained tumor tissue slice is manually magnified by a trained histopathologist through a computer 7,8 . The diagnosis was made by analyzing the morphological variation in the cancerous area, quantifying the density of the malignant area, and observing the spatial arrangement of the tumor microenvironment 9–11 . Nevertheless, the scarcity of pathologists and high clinical experience requirements exacerbate the conflict between clinical demands and actual production.…”
Section: Introductionmentioning
confidence: 99%